Pelatihan penanganan pascapanen rumput laut - Fatmawati Fatmawati; Jasman Jasman; Amal Aqmal (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service activity is the dissemination of seaweed postharvest assistance technology tofarmer groups in Punaga Takalar Village. Application of seaweed postharvest technology is expected to help increase the incomeof seaweed farmers, as a result of community service, it is expected that there will be a change in mindset and protection forfarmers regarding seaweed postharvest handling techniques. The method used in this activity is PRA (Participatory RuralAppraisal), which involves seaweed farmers in the activity. Carry out socialization (counseling), training. The results of theservice show that there are changes in the patterns of thinking and protection patterns of farmers regarding the handling ofseaweed postharvest related to how to handle postharvest seaweed better, and in accordance with improving quality.